How multidimensional poverty went down : dynamics and comparisons - Alkire, S; Roche, J (Oxford Poverty & Human Development Initiative (OPHI), 2013)
Of 22 countries having data on MPI poverty over time, 18 reduced MPI significantly, and most reduced multidimensional poverty faster than income poverty.